MODEL PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN SCIENCE TECHNOLOGY ENGINEERING MATHEMATICS (STEM) DALAM PEMBELAJARAN FISIKA MATERI ELASTISITAS DI KELAS XI MIPA 4 SMA NEGERI 2 JEMBER - Mita Dwi Agustin; Albertus Djoko Lesmono; Heny Mulyo Widodo (Universitas Jember, 2020)
The Problem Based Learning (PBL) model has been applied in Indonesia for a long time. The Problem Based Learning (PBL) model with the approach of Science, Technology, Engineering, and Mathematics (STEM) is new in the world of education. When students are introduced to the new learning model, it will make students have a high curiosity and a great desire to learn. Having a great desire to learn will affect student learning outcomes. Problem Based Learning (PBL) model with the approach of Science, Technology, Engineering, and Mathematics (STEM) is expected to improve student learning outcomes in the cognitive domain. This study aims to describe student learning outcomes using the Problem Based Learning (PBL) model which is integrated with Science, Technology, Engineering, and Mathematics (STEM) on the subject of elasticity. This type of research is a true experimental research design with pretest-posttest control-design conducted in class XI MIPA 4. The conclusion of this study is the Problem Based Learning (PBL) model with the approach of Science, Technology, Engineering, and Mathematics (STEM) can improve student learning outcomes in the cognitive domain in learning physics in class XI MIPA 4 SMA NEGERI 2 JEMBER.